Noh Creation of Shakespeare - Munakata, Kuniyodhi (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
This article contains select comments and reviews on Noh Hamlet and Noh Othello in English and Noh King Lear in Japanese. The scripts from these performances were arranged based on Shakespeare’s originals and directed on stage and performed in English by Kuniyoshi Munakata from the early 1980s until 2014. Also, the whole text of Munakata’s Noh Macbeth in English (Munakata himself acted as Macbeth and Lady Macbeth in one play) is for the first time publicized. The writers of the comments and reviews include notable people such as John Fraser, Michael Barrett, Upton Murakami, Donald Richie, Rick Ansorg, James David Audlin, Jesper Keller, Jean-Claude Saint-Marc, Jean-Claude Baumier, Judy Kendall, Allan Owen, Yoshio ARAI, Yasumasa OKAMOTO, Tatsuhiko TAIRA, Hikaru ENDO, Kazumi YAMAGATA, Hanako ENDO, Yoshiko KAWACHI, Mari Boyd, and Daniel Gallimore.